ANALISIS STUKTUR, KINERJA, DAN PERILAKU INDUSTRI ROKOK KRETEK DAN ROKOK PUTIH DI INDONESIA PERIODE 1991-2008 - Gustyanita Pratiwi; Lukytawati Anggraeni (Jurnal Agribisnis Indonesia, 2013)
Tobacco industry is one of important manufacturing industry in Indonesia. There are several changes in structure, performance, and behavior of this industry during 1991-2008. This study aim is to analyze the differences between clove cigarette and white cigarette industries with SCP method. Analysis of industrial structure with CR4 index and barriers to entry. Industry performance is measured by Price Cost Margin (PCM) approach. Factors that affect the performance itself are analyzed by the Ordinary Least Square (OLS) method. The results of structural analysis show that the level of industry concentration of clove cigarettes went from tight oligopoly (84.29 percent) to medium oligopoly (52.65 percent) during research period. In contrast, white cigarette industry remained in tight oligopoly level with an average value of CR4 about 94.33 percent. The average value of MES which reflects the barrier to entry in white cigarette industries is higher (95.17 percent) than in cigarette industries (72.85 percent). Regression analysis on a clove cigarette industry indicates that the variable X-eff and growth are significantly positive, whereas a variable number of firms significantly negative effect on PCM. In white cigarette industry, a significant variable to the PCM is the X-eff  (0.366799). The analysis of behavior between the two industries cannot be separated from government regulation, especially in setting of the selling price. Promotion, although it increasing production costs, remains to be important strategy to maintain the industry market share.